Functions of the Prosecutor of the Republic of Indonesia in the Eradication of the Crime of Collusion to Create a Clean State Apparatus - Budi H. Panjaitan; J. Ronald Mawuntu; Caecilia J. J. Waha; Jemmy Sondakh (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2022)
This research analyzes how the Prosecutor's Office conducts the eradication of collusion and creates a clean state apparatus to prevent corruption. To examine the rosecutor's office function, a normative research method was used with a sample of the rules and policies issued by the prosecutor's office of the Republic of Indonesia. The findings show that the function of the Prosecutor's Office in eradicating corruption and enforcing the law must be continually carried out through various efforts so that the government projects are right on cost, on time, and of good quality by supervising and securing the planning, implementation, and utilization of development results.Â Keywords: Â Clean State Apparatus, Collusion, Crime Eradication, Functions of the Prosecutor's Office, Normative Legal Research